(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In an increasingly connected world, the internet has become an essential part of daily life, offering opportunities for socializing, learning, and professional advancement. However, this same digital landscape has given rise to a disturbing phenomenon known as "cyber suicide." This term encompasses a wide range of online behaviors that contribute to or directly lead to self-harm or suicide, highlighting the darker side of digital engagement. Social media platforms are a double-edged sword. While they offer support, connection, and a sense of belonging for many, they can also amplify feelings of isolation, inadequacy, and distress. Studies have shown that heavy use of social media is linked to depression, anxiety, and other mental health issues, especially among young people. For individuals struggling with mental health challenges, social media can exacerbate negative emotions by exposing them to cyberbullying, harassment, and toxic comparisons. The constant barrage of curated, idealized content can make users feel inadequate or worthless, creating a dangerous feedback loop that deepens feelings of despair.